Medicinal Plants Used to Treat Oral Diseases in the Lepelle-Nkumpi Municipality, Limpopo Province, South Africa - Sebua Silas Semenya; SekgotheMokgoatšana; Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2019)
Purpose: Therefore, this study was aimed at documenting medicinal plants used to treat oral diseases in the Lepelle-Nkumpi Municipality in the Limpopo Province, South Africa. Methods: Data was collected using a semi-structured questionnaire, supplemented by field observations with 30 traditional healers from the Lepelle-Nkumpi Municipality in the Capricorn District of the Limpopo Province in South Africa. Results: A total of 41 plant species belonging to 30 botanical families, mainly the Asteraceae and Solanaceae (13.3% each), were reported as remedies for different oral diseases. Leaves (51%) and roots (28%), harvested from herbs and trees were preferred for medicinal preparations. The majority of plant species (60.4%) were used as monotherapy, to treat a single oral disease, while the remainder (39.6%) treated more than one ailment. The majority of the species (44.2%) were used as herbal medicines for toothache, followed by 32.6% used against bad breath and 25.6% used against dental caries. Conclusion: Traditional healers play an important role in the provision of primary health care as oral pathogens are also responsible for nonstomatological infections.